The Emergence of Spanking Among a Representative Sample of Children Under 2 Years of Age in North Carolina - Zolotor, Adam J.; Robinson, T. W.; Runyan, Desmond K.; Barr, Ronald G.; Murphy, Robert A. (Frontiers in Psychiatry, 2011)
Spanking is common in the United States but less common in many European countries in which it has been outlawed. Being spanked has been associated with child abuse victimization, poor self-esteem, impaired parent-child relationships, and child and adult mental health, substance abuse, and behavioral consequences. Being spanked as a child has also been shown to increase the likelihood of abusing one’s own children or spouse as an adult. Spanking of very young children less than two is almost never recommended even among experts that consider spanking as reasonable in some circumstances. Using a cross-sectional anonymous telephone survey, we describe spanking rates among a representative sample of North Carolina mothers of children less than two years old and the association of spanking with demographic characteristics. A substantial proportion of mothers admit to spanking their very young children. The rate of spanking in the last year among all maternal respondents was 30%. Over 5% of the mothers of three month olds reported spanking. Over 70% of the mothers of 23 month olds reported spanking. Increased spanking was associated with higher age of the child and lower maternal age. With every month of age, a child had 27% increased odds of being spanked. Early spanking has been shown to be associated with poor cognitive development in early childhood. Further, early trauma has been shown to have significant effects on the early developing brain. It is therefore critical that health and human services professionals addres the risk of corporal punishment as a method of discipline early in the life of the child. The spanking of very young children may be an appropriate locus for policy and legislative debates regarding corporal punishment.